Ultimate strength analysis of stiffened plate structures - Nwoye, McAnthony (My University, 2022)
An international benchmark study on which this thesis is based compared FEA results to a reference experiment. The FEA results and experiment were in agreement with respect to ultimate capacity but not for modes and location of failure. This thesis, therefore, investigates possible factors that impact ultimate capacity, failure mode and location. This was achieved analytically and by non-linear finite element analysis. The method employed was to systematically alter the geometry used in the benchmark study and then observe the changes that influenced the results. The ultimate capacity of some of these models was also calculated by implementing existing empirical models in python. The models were then subjected to linear and non-linear buckling analysis in Abaqus. The results are presented as force–displacement curves and von Mises stress plots. The ultimate capacity was shown to be sensitive to longitudinal stiffener configuration, longitudinal stiffener dimensions, bottom plate configuration and bottom plate thickness. The empirical estimation of ultimate capacity was shown to be quite conservative when compared to the FEA prediction. The failure location however was found to be most sensitive to the bottom plate configuration. Models with uniform bottom plate field thickness had an influence on the location of failure. Most importantly, two of the models with uniform bottom plate fields studied predicted the failure location recorded in the reference experiment. The effects of the boundary conditions and direction of force application prescribed are also documented.
Keywords: failure location; linear buckling analysis; non-linear finite element analysis; ultimate capacity